Benefits, challenges, and best practices of collaborative partnerships among health supply chain stakeholders in Rwanda: a cross-sectional study - Anitha Tuyishime; Innocent Hahirwa; Kato Jonas Njunwa; John Nyiligira (BMC Health Services Research)
Abstract Background Strong partnerships, community engagement, and multisectoral collaboration in the health supply chain are synergistic pillars towards achieving universal health coverage. In Rwanda, the health supply chain involves the collaboration of various stakeholders, including distributors, manufacturers, wholesalers, and customers. However, since the eruption and ending of COVID-19, there has not been any study to assess stakeholders' perspectives on the status of the benefits, challenges, and best practices of collaborative partnerships among health supply chain stakeholders in Rwanda. Therefore, this research was conducted to fill that gap in order to devise ways for improved visibility, coordination, and efficiency of the health supply chain management system in Rwanda. Methods This quantitative cross-sectional study, collected data from 11th April to 18th May 2024. It involved 103 respondents from 54 institutions engaged in the management of the health commodities supply chain in Rwanda. These were the Ministry of Health, Rwanda Biomedical Center, Rwanda Food and Drugs Authority, Rwanda Medical Supply Ltd, other Central Medical Stores namely Bureau des Formations Médicales Agréées du Rwanda (BUFMAR) and Medical and Allied Service Solutions (MEDIASOL); private wholesale pharmacies, non-government organizations, and Health Facilities (hospitals). A sample size of 103 respondents was determined by the Yamane formula, and purposive sampling was used to select the respondents to complete a self-administered questionnaire specifically developed for this study. The outcome measures were perceived benefits, challenges, and strategies to overcome challenges of collaborative partnerships among health supply chain stakeholders in Rwanda. Results Availability of health commodities ranked at 98.0%, infrastructure/accessibility of health services (86.4%), and cost-effectiveness (84.5%) were the most mentioned benefits. Most stated challenges included insufficient financial resources from stakeholders (84.5%), shortage of skilled staff (77.7%), and limited dialogue or lack of information sharing (69.9%). Most respondents agreed that collaborative partnerships can be improved by political will (96.1%), supply performance measurement (92.2%), improved financing policies (84.5%), fostering trust and transparency building (78.6%), and a well-structured health supply chain (72.5%). Conclusion Establishing and strengthening stakeholder collaborations are essential for improved performance. Staff capacity strengthening and mutual information sharing will reduce risks, and improve forecasting, leading to cost-effectiveness and customer satisfaction.